2011
DOI: 10.1186/1471-2296-12-55
|View full text |Cite
|
Sign up to set email alerts
|

Attitude toward contraception and abortion among Curaçao women. Ineffective contraception due to limited sexual education?

Abstract: BackgroundIn Curaçao is a high incidence of unintended pregnancies and induced abortions. Most of the induced abortions in Curaçao are on request of the woman and performed by general practitioners. In Curaçao, induced abortion is strictly prohibited, but since 1999 there has been a policy of connivance. We present data on the relevance of economic and socio-cultural factors for the high abortion-rates and the ineffective use of contraception.MethodsStructured interviews to investigate knowledge and attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…The present research supports the notion that sexual sin is related to greater self-sacrifice. In Study 1, we demonstrated that the underlying mechanism of this effect is sexual guilt, which confirms insights from previous research on an emotion that suggests that guilt is associated with reparative behavior (e.g., Tangney et al, 1992). In Study 2, we demonstrated that when recalling a sinful experience, people with intrinsic (as opposed to extrinsic) religious motivation adopted a more vengeful and ruthless cognitive representation of God.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The present research supports the notion that sexual sin is related to greater self-sacrifice. In Study 1, we demonstrated that the underlying mechanism of this effect is sexual guilt, which confirms insights from previous research on an emotion that suggests that guilt is associated with reparative behavior (e.g., Tangney et al, 1992). In Study 2, we demonstrated that when recalling a sinful experience, people with intrinsic (as opposed to extrinsic) religious motivation adopted a more vengeful and ruthless cognitive representation of God.…”
Section: Discussionsupporting
confidence: 84%
“…Psychological research indicates that religious involvement is positively associated with the experience of guilt (Luyten, Corveleyn, & Fontaine, 1998;Nelsen & Kroliczak, 1984)-an emotion aroused by transgressing religious moral values and norms (i.e., committing a sin). According to Tangney (1990;Tangney, Wagner, Gramzow, 1992), guilt prompts people to repair their wrongdoings and avoid harming others in the future. From that standpoint, guilt is adaptive as it promotes harmonious interpersonal relationships.…”
Section: The Experience Of Sin and Guiltmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible association between contraceptives (including condom) and sexual function remains controversial in the literature. It has been reported that women may experience positive effects [10] , negative effects [11] , or no effects [12,13] on libido and other parameters of sexual function during contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the attention to sexual health in the Caribbean, as in many other geographical contexts, has been limited and fragmented. The current scientific literature (last 3 years) covering sexual health areas in the Caribbean is mostly associated with reproductive health (Boersma et al 2012;Claeys 2010;Ferguson et al 2012;Pottinger et al 2012;Priestley 2012;van den Brink et al 2011), sexual violence (Cobbett and Warrington 2013;Lucea et al 2013;van Wijk and de Brujn 2012), sexuality education (Escobar-Chaves et al 2011;Hammer et al 2010), sexual behaviors (Anastario et al 2010;Ishida et al 2011;Ortiz et al 2011), sexually transmitted infections (excluding HIV) (Anderson et al 2013;Orisatoki and Oguntibeju 2010;Underwood et al 2010), and other sexual health concerns and problems, particularly cancers (Hennis et al 2013;Chekuri et al 2012;Méndez et al 2013;Underwood et al 2010). In these recent articles, some island nations or populations are more represented than others and we can speculate that this is associated with the involvement of the academic institutions in these countries as well as the resources allocated for research and dissemination of findings.…”
Section: Introductionmentioning
confidence: 99%